2024
DOI: 10.1101/2024.03.05.583526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Matrix viscoelasticity controls epithelial cell mechanobiology through dimensionality

Giuseppe Ciccone,
Mariana Azevedo Gonzalez Oliva,
Marie Versaevel
et al.

Abstract: In recent years, matrix viscoelasticity has emerged as a potent regulator of fundamental cellular processes and has been implicated in promoting cancer progression. Alongside viscoelasticity, additional ECM cues have been shown to influence migration decision-making of cancer cells, and spatial confinement is now considered as a potential regulator of metastasis. However, our understanding of these complex processes predominantly relies on purely elastic hydrogels, and the exact relationship between matrix vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…These processes are in accordance with literature describing cell interaction with stiff 2D viscoelastic substrates. Indeed, our group has demonstrated that cell motility is reduced in epithelial cells in response to enhanced substrate stress relaxation at E > 1kPa 45 . Similarly, at stiffness E > 1kPa, we have shown that viscoelasticity reduces cell spreading area, molecular clutch engagement and YAP nuclear translocation, which are all processes involved in bone remodelling.…”
Section: Resultsmentioning
confidence: 96%
“…These processes are in accordance with literature describing cell interaction with stiff 2D viscoelastic substrates. Indeed, our group has demonstrated that cell motility is reduced in epithelial cells in response to enhanced substrate stress relaxation at E > 1kPa 45 . Similarly, at stiffness E > 1kPa, we have shown that viscoelasticity reduces cell spreading area, molecular clutch engagement and YAP nuclear translocation, which are all processes involved in bone remodelling.…”
Section: Resultsmentioning
confidence: 96%